2019
DOI: 10.1002/mar.21300
|View full text |Cite
|
Sign up to set email alerts
|

Anticonsumption beyond consumers: The role of small organic producers in environmentally oriented anticonsumption

Abstract: Recent studies recognize that environmentally oriented anticonsumption gives power to individuals who are willing to express their environmental concerns. Yet, it goes beyond consumers' decisions and should also include producers' practices and discourses. In this study, we explore the food system context and the emergence of organic food as a more sustainable and healthy food production mode to describe the role of organic farmers in building social and material arrangements against conventional food producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 62 publications
0
10
0
6
Order By: Relevance
“…Most studies have focused on the environmental dimension of sustainable food consumption. This has received a lot of attention in the marketing and consumption arena, including the tourism context (Cachero‐Martínez, 2020; Chang et al, 2021; Dalmoro et al, 2020; Nam, 2020; Rothwell et al, 2016; Shashi & Singh, 2015; Shin et al, 2017). Shashi and Singh (2015) showed that biodiversity preservation, conservation of natural resources and lower energy consumption play key roles in influencing consumer purchasing intentions towards organic foods.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Most studies have focused on the environmental dimension of sustainable food consumption. This has received a lot of attention in the marketing and consumption arena, including the tourism context (Cachero‐Martínez, 2020; Chang et al, 2021; Dalmoro et al, 2020; Nam, 2020; Rothwell et al, 2016; Shashi & Singh, 2015; Shin et al, 2017). Shashi and Singh (2015) showed that biodiversity preservation, conservation of natural resources and lower energy consumption play key roles in influencing consumer purchasing intentions towards organic foods.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To encourage sustainable consumption, retailers might consider offering special discounts on items (e.g., green cosmetics, ethical clothing) of interest to daughter–mother pairs to stimulate intra‐family communication about intergenerational shopping. And while producers, such as organic farmers, help to promote environmentally oriented anticonsumption practices and alternative consumption systems (Dalmoro et al, 2020), they should keep in mind the important role played by younger generations in changing the consumption patterns of older ones.…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, sustainable consumer behaviors consist of a wide range of activities, potentially involved in nearly all spheres of life. Consumer research exists on various behaviors and activities such as energy‐saving and water‐saving (Gadenne et al, 2011; Gilg & Barr, 2006), sustainable product choice (Liang & Guo, 2021; Tanner & Wölfing Kast, 2003), sustainable dieting (Werner et al, 2019), sustainable giving (Ha‐Brookshire & Hodges, 2009), eco‐clothing (Niinimäki, 2010), sustainable transportation (Hartl et al, 2018), and environmentally oriented anticonsumption of food (Dalmoro et al, 2020), among others. Nonetheless, research on sustainable consumer attitudes and behaviors is equivocal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Esto ha motivado al desarrollo de investigaciones que revelan características y particularidades de un consumidor más consciente, y con un alto grado de sensibilidad social; el que se identifica por ser solidario, empático y juicioso de sus acciones (Hosta y Žabkar, 2016;Barragán y Ayaviri, 2018). Lo que, además, se vincula con los perfiles de anti-consumo (Ashraf et al, 2019;Dalmoro et al, 2020). A su vez, dedica parte de sus esfuerzos en reducir los efectos medioambientales, lo que conduce a la consideración sentida de las necesidades de las generaciones futuras, en relación a la satisfacción de sus propias necesidades (Fernández y Gutiérrez, 2013;Kiss et al, 2018;Scott y Weaver, 2018).…”
Section: Introductionunclassified